A comprehensive review on rice responses and tolerance to salt stress - Sackey, Obed Kweku; Feng, Naijie; Mohammed, Yushawu Zakaria; Dzou, Chrystella Fernanda; Zheng, Dianfeng; Zhao, Liming; Shen, Xuefeng (Frontiers in Plant Science, 2025)
The challenge of salinity stress significantly impacts global rice production, especially in coastal and arid regions where the salinization of agricultural soils is on the rise. This review explores the complex physiological, biochemical, and genetic mechanisms contributing to salinity tolerance in rice (Oryza sativa L.) while examining agronomic and multidisciplinary strategies to bolster resilience. Essential adaptations encompass the regulation of ionic balance, the management of antioxidants, and the adjustments to osmotic pressure, all driven by genes such as OsHKT1;5 and transcription factors like OsbZIP73. The evolution of breeding strategies, encompassing traditional methods and cutting-edge innovations, has produced remarkable salt-tolerant varieties such as FL478 and BRRI dhan47. The advancements in this field are enhanced by agronomic innovations, including integrated soil management, crop rotation, and chemical treatments like spermidine, which bolster stress tolerance through antioxidant activity and transcriptional regulation mechanisms. Case studies from South Asia, Sub-Saharan Africa, the Middle East and, Australia demonstrate the transformative potential of utilizing salt-tolerant rice varieties; however, challenges persist, such as the polygenic nature of salinity tolerance, environmental variability, and socioeconomic barriers. The review highlights the importance of collaborative efforts across various disciplines, merging genomic technologies, sophisticated phenotyping, and inclusive breeding practices to foster climate-resilient and sustainable rice cultivation. This work seeks to navigate the complexities of salinity stress and its implications for global food security, employing inventive and cohesive strategies to confront the challenges posed by climate change.